Jitter That Occurred in the Flight Management System During the Vor Operational Check Using the Aeroflex IFR-4000 on the Beechcraft King Air 350I Aircraft - Muhammad Ihsan (CV Media Inti Teknologi, 2025)
Background of study: Ensuring the proper functioning of the Flight Management System (FMS) is crucial for flight safety, particularly during VOR Operational Checks. Jitter in the FMS can disrupt navigation and compromise the accuracy of flight operations. During an On-the-Job Training (OJT) program at the Balai Besar Kalibrasi Fasilitas Penerbangan (BBKFP), jitter was identified in the FMS of a Beechcraft King Air 350i during a VOR Operational Check using the AeroFlex IFR-4000. Aims and scope of paper: This paper aims to analyze and identify the cause of FMS jitter observed during VOR Operational Checks on the Beechcraft King Air 350i using the AeroFlex IFR-4000. The scope of the study is limited to the analysis of jitter occurrence during the VOR Operational Check process. Methods: A qualitative descriptive method was applied by analyzing data obtained from direct observation of the VOR Operational Check and referencing the aircraft maintenance manual. The analysis particularly examined the relationship between RF signal strength from the AeroFlex IFR-4000 and the occurrence of FMS jitter. Result: The study found that FMS jitter during the VOR Operational Check was caused by low RF signal levels generated by the AeroFlex IFR-4000. Adjusting the RF signal level from -10 dBm to -5 dBm successfully eliminated the jitter issue. Conclusion: FMS jitter has a direct impact on navigational accuracy and thus requires immediate attention during operational checks. This research emphasizes the importance of ensuring adequate RF signal strength in order to prevent FMS jitter, thereby maintaining reliable navigation and flight safety.